2010
DOI: 10.1039/c002905j
|View full text |Cite
|
Sign up to set email alerts
|

Ultraefficient separation and sensing of mercury and methylmercury ions in drinking water by using aminonaphthalimide-functionalized Fe3O4@SiO2 core/shell magnetic nanoparticles

Abstract: A new fluorogenic based aminonaphthalimide-functionalized Fe(3)O(4)@SiO(2) core/shell magnetic nanoparticles 1 has been prepared, and its abilities to sense and separate metal ions were evaluated by fluorophotometry. The nanoparticles 1 exhibited a high affinity and selectivity for Hg(2+) and CH(3)Hg(+) ions over competing metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(31 citation statements)
references
References 22 publications
0
27
0
4
Order By: Relevance
“…ions are coordinated It should be noted that in recent years in the literature there is considerable interest to development of magnetic adsorbents, in particular, based on magnetite, as well as to the study of their properties and modeling processes occurring on the surface. Thus, adsorption by magnetosensitive nanocomposites and by modified surfaces of different chemical nature has been studied with respect to heavy metal ions [36][37][38][39], organic and biological molecules [40][41][42][43], and anti-cancer drugs [44][45][46]. Clarification of mechanisms and theoretical modeling of platinum complexes adsorption on the surface of synthesized nanostructures with considering of the surface state, the nature of the surface active centers and their concentration, will be performed by us later.…”
Section: Resultsmentioning
confidence: 99%
“…ions are coordinated It should be noted that in recent years in the literature there is considerable interest to development of magnetic adsorbents, in particular, based on magnetite, as well as to the study of their properties and modeling processes occurring on the surface. Thus, adsorption by magnetosensitive nanocomposites and by modified surfaces of different chemical nature has been studied with respect to heavy metal ions [36][37][38][39], organic and biological molecules [40][41][42][43], and anti-cancer drugs [44][45][46]. Clarification of mechanisms and theoretical modeling of platinum complexes adsorption on the surface of synthesized nanostructures with considering of the surface state, the nature of the surface active centers and their concentration, will be performed by us later.…”
Section: Resultsmentioning
confidence: 99%
“…Among these approaches, solid phase extraction is recognized to be superior to the others, in terms of simplicity, flexibility, time-saving, and low cost [6,8]. Recently, solid phase extraction with magnetic composites has been subjected to extensive research, because of their wide applications in enzyme immobilization [19], DNA extraction [20], targeted drug delivery [21], and pre-concentration/removal of various metal ions [6,16,17,[22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the magnetic force directing particles toward magnet is proportional to magnetic field gradient as well as to magnetization and volume of the particles [28,30], encapsulation of magnetite nanoparticles into nonmagnetic matrix is an alternative strategy to construct magnetic composites with enhanced volume, and hence high magnetization and superparamagnetism. As for surface functionality, amino groups upon magnetic composites have been well documented to facilely combine with metal clusters [31], metal ions [22][23][24][25][26][27][28], drug [32], and biomolecules [20]. In view of polyaniline (PANI) and polypyrrole (PPy) being eco-friendly and wealthy in amino groups, Fe 3 O 4 /PANI and Fe 3 O 4 /PPy composite microspheres with core-shell structure and superparamagnetism have attracted much attention on the basis of their excellent performance in DNA extraction [20] and metal ion removal [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [28] showed a multifunctional magnetic mesoporous silica nanocomposite with improved sensing performance and effective removal ability toward Hg 2+ , which was prepared by the immobilization of a pyrene-based receptor within its channels. Park et al [27] reported an ultraefficient separation and sensing of mercury and methylmercury ions in drinking water by using aminonaphthalimide-functionalized Fe 3 O 4 @SiO 2 . Liu et al [29] also developed humic acid-modified Fe 3 O 4 magnetic nanoparticles and employed them in magnetic confinement assays to isolate Hg 2+ , Pb 2+ , Cu 2+ , and Cd 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Functionalized nanoparticles are of great interest for environmental research applications because they are easily renewable and are stable against degradation [27]. Meanwhile, magnetic Fe 3 O 4 nanoparticles are of increasingly significant importance for sewage treatment.…”
Section: Introductionmentioning
confidence: 99%